Contribution of PNPLA3 gene polymorphisms to hepatocellular carcinoma susceptibility in the Chinese Han population - Dongwei Gong; Shizong Li; Zhiwei Yu; Kaiqiong Wang; Xin Qiao; Changxiong Wu (BMC Medical Genomics, 2022)
Abstract Objectives The purpose of this study was to investigate the association of PNPLA3 single nucleotide polymorphisms (SNPs) (rs738409 C > G, rs3747207 G > A, rs4823173 G > A, and rs2896019 T > G) with hepatocellular carcinoma (HCC) susceptibility. Methods This case–control study included 484 HCC patients and 487 controls. Logistic regression analysis was performed to study the associations of PNPLA3 gene polymorphisms with HCC susceptibility, and odds ratios with their corresponding 95% confidence intervals were calculated to evaluate these correlations. Results In the overall analysis, we found that the G allele (OR = 1.25, 95% CI = 1.04–1.50, p = 0.018, false discovery rate (FDR)-p = 0.035) and GG genotype (OR = 1.59, 95% CI = 1.06–2.39, p = 0.024, FDR-p = 0.048) of rs2896019 were significantly associated with increased HCC susceptibility. In stratified analysis, we found that all four SNPs were related to increased HCC susceptibility in subjects aged > 55 years. In haplotype analysis, the GAAG haplotype was significantly associated with increased HCC susceptibility (OR = 1.25, 95% CI = 1.03–1.53, p = 0.023, FDR-p = 0.046). Besides, we noticed that rs738409 was significantly correlated with alpha-fetoprotein (AFP) (p = 0.007), and HCC patients with the GG genotype had a higher level of AFP. Conclusions Our study suggested that PNPLA3-rs2896019 was significantly associated with an increased susceptibility to HCC.